Enhancement of Entrepreneurship Skill for Universitas Muhammadiyah Magelang Students - Setiawan, Agus; Al Manan, Oesman Raliby; Primadewi, Ardhin; Purnomo, Tuessi Ari (Muhammadiyah University Press, 2018)
Universitas Muhammadiyah Magelang (UMMgl) has a vision of